Leadership Style Versus Innovativeness of High Technology Enterprises - Dorota SOBOL (Communications of International Proceedings, 2021)
The studies of the subject literature and the results of existing research emphasize the importance of the so-called ‘soft’ aspects of management in the context of innovativeness of modern enterprises. Organizational innovativeness is the result of cooperation, creativity and commitment of employees, therefore, the analysis of the impact identified in B.M. Bass styles of leadership for innovation is extremely important, though underestimated. The aim of the article was to recognize the importance of the leadership style on the innovation of small and medium-sized enterprises representing the high-tech sectors. Basic research to achieve the goal was carried out using the survey method. Research has provided evidence of which leadership behavior promotes innovation and which should be avoided. The directions of further research were also indicated.
Keywords: Determinants of Innovation; Leadership; High-Technology Enterprises